Discursive ethics and political democracy (1993)
Discursive ethics or communicative ethics were born in the seventies fathered by K.O. Apel and J. Habermas, and today they are widely known; it is a current of such life and vigour that its very creators have engaged in lively polemics. This paper, starting from K.O. Apel' s texts, attempts to explore in what measure this discursive ethics provides philosophical foundations for political democracy and to determine the basic elements  necessary for the construction of a universal ethics.